Functionalized Amyloid‐Like Protein Nanofilm‐Mediated Synergistic Disulfidptosis and Photodynamic Therapy for Preventing Postoperative Recurrence of Colorectal Cancer - Man Zhang; Ke Li; Junhao Kou; Guozhi Lu; Ling Qiu; Chunzhao Yang; Yongchun Liu; Qi Xue; Peng Yang (Small Science)
Colorectal cancer (CRC) has a postoperative recurrence rate of up to 50%. Local treatment at the surgical site offers a new strategy to prevent recurrence, minimizing systemic side effects. However, these treatments often face issues like poor stability, insufficient targeting, and significant local side effects. Research shows glucose starvation can induce disulfidptosis, a novel cell death pathway, in CRC cells, suitable for precise intervention in residual tumor cells postsurgery. This study develops a biocompatible 2D therapeutic platform using amyloid‐like protein nanofilm technology for precise local synergistic intervention in disulfidptosis and photodynamic therapy (PDT) after CRC surgery. The nanofilm boasts excellent drug‐loading capacity, enzyme activity retention, ultrathin dimensions, wet adhesion, and biocompatibility. A model simulating incomplete tumor resection post‐CRC surgery shows that the GCI@nanofilm effectively inhibits recurrence through an enzyme‐catalyzed cascade reaction inducing disulfidptosis and synergizing with PDT. In summary, GCI@nanofilm overcomes multiple challenges in local postsurgical intervention, providing a foundation for precise and efficient treatment of residual tumors.